Light Chain Isotype and Antibody-Specificity Impact on Virus Neutralization - Sun, Lin; Palt, Roman; Schütz, Georg; Föderl-Höbenreich, Esther; Brod, Laura; Hermle, Antonia; Lux, Anja; Steinkellner, Herta; Kallolimath, Somanath (Antibodies, 2025)
Therapeutic antibodies with lambda light chains (λ-Abs) are underrepresented compared to kappa light chains (κ-Abs). Here, we evaluated two SARS-CoV-2-specific monoclonal antibodies (mAbs) that exhibit high (P5C3) and low (H4) antigen binding as κ and λ variants. mAbs expressed in glycoengineered Nicotiana benthamiana did not show differences in expression levels, glycosylation, and antigen binding, while κ-Abs exhibited slightly increased thermodynamic stability over λ-Abs. SARS-CoV-2 neutralization and IgG-FcγR immune complex studies revealed increased activities of H4 IgG1κ compared to H4 IgG1λ, with no differences observed between P5C3 variants. Our results indicate that constant light chain variability and Ab specificity contribute to Ab features, a fact that should be considered in engineering therapeutics.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Fcγ-receptor binding; kappa–lambda light chain; monoclonal antibodies; SARS-CoV-2; stability; virus neutralization